The Role of Digital Accounting in the GIG Economy and Creative Industries - Nurhanimah; Alan Budi Kusuma; Nur Baiti (CV. Ulil Albab Corp, 2025)
The development of digital technology has spurred the emergence of new economic models, including the gig economy and the creative industry, both of which rely on flexibility and innovation. However, both sectors face significant challenges, such as income uncertainty for gig workers and limited access to financing for creative industry players. This study aims to analyze the role of digital accounting in supporting the sustainability of the gig economy and the creative industry. The method used is a literature review with a descriptive qualitative approach, based on primary and secondary literature published between 2021 and 2025. The results of the study indicate that digital accounting plays a crucial role in enhancing the financial legitimacy of gig workers through real-time transaction recording, tax calculation, and increased access to formal financial services. In the creative industry, digital accounting strengthens the credibility of financial reports, opens access to financing, and supports data-driven business strategies. In conclusion, digital accounting functions not only as a recording tool but also as a strategic instrument that strengthens an inclusive, sustainable, and globally competitive digital economic ecosystem.